Studi Komparatif Tentang Metode Menghafal Al Qur’an Antara PP. Putri Al Munawir Komplek “Q” dengan PP. Putri Ali Maksum Krapyak Bantul Yogyakarta - Sukati . (Universitas Alma Ata, 2015)
Abstract This study aims to determine: Qur’an memorization method used in PP. Daughter Al Munawwir Complex “Q” and the PP. Daughter Ali Maksum Krapyak Bantul, Yogyakarta, differences and similarities, factors that support and hinder the results achieved in memorizing the Koran in both the PP. Daughter Al Munawwir Complex “Q” or PP. Daughter Ali Maksum Krapyak Bantul, Yogyakarta. This research includes a comparative descriptive research with 59 students in PP Putri Al Munawwir Krapyak Komplek Q and 61 students PP Putri Ali Maksum. Collecting data using observation method, method Interview (Interview), Methods Questionnaire, and Documentation. And data analysis using qualitative and quantitative methods. The results showed that: The method of teaching to memorize the Qur’an used in PP. Daughter Al Munawwir Complex “Q” is Tahfidz method with Qiro’ati method, method in memorize of juz amma binnadzor method juz 1, musyafadah method with one by one. Takrir method with musyafahah method in pairs, group method, estafet method, seaman method. Methods of proof with musyafahah with pairwise method, the method group, a relay method, the method Semaan. Teaching method in memorize of Qur’an used in PP Putri Ali Maksum are Method Tahfidz with binnadzri method, Method musyafahah with five-five. Methods of proof with musyafahah method with one by one, Methods jam’u al, Methods istima’i (Semaan) Friday legi, pray method. The diffeences of those located in the implementation and the similarities located using two methos, tahfidz method and takrir method. Factors that support in memorize of Quran in PP Putri Al Munawwir komplek Q : workship Allah, and preserve purity of Quran, 67.80% ; memorize when there is free time 49,15% memorize because of support by situation and condition 47,46%. While factor that support in memorize of Quran 65,57%; memorize when the mind is quiet 59,02% and situation that support 44,26%. Factors that block in PP Putri Al Munawwir komplek Q, sometimes the student has difficulties to memorize of Quran and can not consentrate (59,02%) and they must to repeat the memoriez of Quran 37,70%. the result achieved in memorize of Quran in PP Putri Al Munawwir complex Q in daily routine, not more than 64,61% and they don’t have a brave listened by the master of Quran yet. While in PP Putri Ali Maksum in daily routine, not more than 65,57% and they a brave listened by the master of Quran. Keyword: comparative, memorization method